Composite antibacterial film-forming liquid, preparation method and application thereof
Patent Information
- Application Number
- CN202611397786.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-30
AI Technical Summary
但该体系仍存在不足:热压工艺需120℃高温高压,不适用于抗菌活性填料的复合改性;薄膜水蒸气透过率显著升高,耐湿性能较差,高湿条件易吸水溶胀;未开展生鲜食品实际保鲜评价,限制了其在生鲜活性包装领域的应用
[0029](1)本发明采用低共熔溶剂与甘油复配作为协同增塑体系,可有效削弱壳聚糖分子链间的强氢键作用,在改善纯壳聚糖成膜脆性大、韧性不足缺陷的同时,避免了单一增塑剂改性导致的薄膜水溶解度升高、耐湿性能下降问题,使所得复合抗菌纸同时兼具优异的机械韧性与水汽阻隔性能,适配高湿生鲜食品的包装场景。
Smart Images

Figure CN123005752A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of food packaging technology, and specifically discloses the preparation method and application of antibacterial film-forming liquid and its antibacterial paper. Background Technology
[0002] With the rapid development of the global food industry, microbial contamination and post-harvest spoilage have become core challenges restricting the preservation of fruits and vegetables and ensuring food safety. Fresh meat and fresh fruits and vegetables are high-moisture, high-nutrient, and easily perishable foods. During storage, transportation, and sales, they are highly susceptible to microbial contamination, leading to mold and spoilage, causing not only huge economic losses but also serious food safety hazards. To reduce damage caused by mechanical impact and microbial growth due to juice seepage during cold chain storage and transportation of fresh food, packaging materials are typically used for simple wrapping and padding. This provides physical cushioning to reduce mechanical damage and absorbs some of the seeping juice, slowing down microbial growth and reducing the risk of cross-contamination. Currently, the main packaging materials used include plastic, paper, metal, and glass. Plastic packaging offers good preservation but is difficult to degrade and easily causes microplastic pollution, which does not conform to the concept of green and sustainable development and has been gradually replaced by green and biodegradable packaging materials. Metal and glass packaging, due to their extreme weight, high transportation costs, and lack of antibacterial and preservation functions, have limited application scenarios and insufficient practicality, making them unsuitable for the distribution and preservation of fresh fruits, vegetables, and meat. Paper-based materials, with their advantages of wide availability, low price, biodegradability, safety, non-toxicity, and good air permeability, have become a research hotspot in food active packaging materials, and have broad application prospects in the preservation of perishable foods such as fresh fruits and vegetables and fresh meat. However, pure paper materials are highly hydrophilic, have poor barrier properties, and lack antibacterial and antifouling functions, making them extremely prone to bacterial growth and stain absorption, and unable to effectively inhibit the spoilage of fresh food, which seriously limits their large-scale application in food preservation packaging.
[0003] With the development of green packaging and active preservation technologies, natural biodegradable polymer packaging materials have gradually become a research hotspot. Chitosan (CS) is a cationic polymer composed of 2-amino-2-deoxy-(1,4)-β-D-glucosamine units. As a natural biopolymer, it possesses excellent biocompatibility, biodegradability, and broad-spectrum antibacterial activity, making it an ideal natural substrate for preparing antibacterial preservation films. However, its film-forming toughness is insufficient and its dispersibility is poor. Introducing polymers, essential oils, and nanofillers can effectively improve the mechanical properties, water vapor permeability, and antibacterial properties of CS. Deep eutectic solvents (DES) can be generated by precisely combining hydrogen bond donors and acceptors in a specific molar ratio, exhibiting advantages such as low toxicity, biodegradability, and excellent solubility. Introducing deep eutectic solvents into chitosan can improve the flowability, tensile strength, ductility, and antioxidant capacity of chitosan films, thereby improving their mechanical and antibacterial properties. Galvis-Sánchez AC, Sousa AMM, Hilliou L, et al. Thermo-compression molding of chitosan with deep eutectic mixture for biofilms development [J]. GreenChemistry, 2016, 18(6): 1571-80. This paper discloses a chitosan film system prepared by hot pressing, which improves the flexibility and light transmittance of the film after adding a choline chloride-citric acid eutectic component. However, this system still has shortcomings: the hot pressing process requires high temperature and high pressure at 120℃, which is not suitable for the composite modification of antibacterial active fillers; the water vapor permeability of the film is significantly increased, resulting in poor moisture resistance and easy water absorption and swelling under high humidity conditions; and no actual preservation evaluation of fresh food has been carried out, limiting its application in the field of fresh food active packaging. Li Li, Pu S, Fan Z, et al. Sodium selenite / selenopeptidechitosan antioxidant film for postharvest preservation of grape [J]. FoodChemistry: X, 2026, 35: 103785. This paper discloses a preservation film prepared by plasticizing and modifying chitosan film with choline chloride-citric acid eutectic solvent and introducing sodium selenite and selenopeptide, which shows certain effects in the preservation of grapes at room temperature.However, the system still has many shortcomings: the prepared composite film has increased water solubility and swelling, poor water resistance, and high water vapor permeability. In high humidity fresh food environments, the film is prone to water absorption, swelling and damage; the preservation evaluation only carried out grape storage experiments under normal temperature conditions, and lacked application verification of cold chain refrigeration; the migration safety of selenium components used in food contact packaging has not been systematically evaluated.
[0004] Glycerin contains multiple hydroxyl groups, which can form intermolecular hydrogen bonds with the amino and hydroxyl groups on chitosan molecules. This weakens the strong hydrogen bonding between chitosan chains, effectively reducing film crystallinity, improving molecular chain fluidity, and mitigating the defects of chitosan films such as brittleness and easy cracking. Glycerin has excellent biocompatibility, meets food packaging safety requirements, is widely available, and inexpensive. Furthermore, glycerin can improve the spreading properties of chitosan film-forming solutions, facilitating the preparation of continuous and complete films. Chen SJ, Zeng QY, Tan XY, et al. Photodynamic antibacterial chitosan / nitrogen-doped carbon dots composite packaging film for food preservation applications[J]. CarbohydratePolymers, 2023, 314: 120938. This paper discloses the preparation of chitosan / nitrogen-doped carbon dots (CS / N-CDs) composite films using a casting method. Glycerol is used as a plasticizer to improve the brittleness of the chitosan film. N-CDs enhance the mechanical properties of the film through hydrogen bonding and possess visible light-driven photodynamic antibacterial and ultraviolet shielding functions, showing certain preservation effects in the preservation of pork and blueberries. However, this system still has significant limitations: N-CDs are rich in hydrophilic groups, resulting in increased water vapor permeability and decreased moisture resistance of the film, leading to severe water loss when used for high-moisture meats; and the safety of the film for food contact packaging was not investigated. Xiao F, Xiao YW, Ji W, et al. Photocatalytic chitosan-based bactericidal films incorporated with WO3 / AgBr / Ag and activated carbon for ethylene removal and application to banana preservation[J]. Carbohydrate Polymers, 2024,328:121681. This paper discloses a WO3 / AgBr / Ag ternary Z-type photocatalyst incorporated with activated carbon into a chitosan matrix, using glycerol as a plasticizer to prepare a multifunctional photocatalytic chitosan film, which showed a certain preservation effect in the preservation of bananas at room temperature. However, this system still has obvious limitations: the introduction of activated carbon deteriorates the film's mechanical properties and water vapor barrier properties, and its application to high-moisture meats will exacerbate moisture loss, making it unsuitable for long-term storage of juicy meats; silver bromide poses a risk of photocorrosion, and its safety has not yet been systematically evaluated. Summary of the Invention
[0005] To address the above shortcomings, the present invention provides a composite antibacterial film-forming liquid with excellent antibacterial, antifouling, and self-cleaning functions, good preservation effect, and biodegradability.
[0006] The second objective of this invention is to provide a method for preparing the above-mentioned composite antibacterial film-forming liquid. This method is simple to operate, has mild conditions, is environmentally friendly, and the resulting composite antibacterial film-forming liquid is uniformly dispersed and has good stability, making it suitable for industrial production.
[0007] The third objective of this invention is to provide an antibacterial paper, which is prepared by impregnating packaging paper with the above-mentioned composite antibacterial film-forming liquid, and has excellent antibacterial properties, antifouling and self-cleaning properties, and good biodegradability.
[0008] The fourth objective of this invention is to provide the application of the above-mentioned antibacterial paper in food packaging materials, especially suitable for the preservation packaging of fresh fruits and vegetables and fresh meat.
[0009] Therefore, the first technical solution provided by this invention is as follows:
[0010] A method for preparing a composite antibacterial film-forming liquid includes the following steps:
[0011] (1) Dissolve chitosan in an aqueous acetic acid solution to obtain a chitosan solution;
[0012] (2) Add a eutectic solvent to the chitosan solution, stir at room temperature, then add glycerol and stir until the solution is uniform and transparent to obtain a CSDG solution; wherein,
[0013] (3) Add the Ag / ZIF-8 / g-C3N4 composite material to a CSDG solution accounting for 10%-30% of the total mass of the CSDG solution and ultrasonically disperse until there is no obvious agglomeration. Then add the remaining CSDG solution and stir at room temperature until the system is uniform to obtain the composite antibacterial film-forming liquid.
[0014] Furthermore, in the preparation method of the above-mentioned composite antibacterial film-forming liquid, in step (1), the ratio of chitosan to the aqueous acetic acid solution is 0.5-1.0 g:50 mL, and the aqueous acetic acid solution is a 0.5% (v / v) glacial acetic acid aqueous solution.
[0015] Furthermore, in the preparation method of the above-mentioned composite antibacterial film-forming liquid, in step (2), the eutectic solvent is composed of choline chloride and citric acid in a molar ratio of 1:1.
[0016] Furthermore, in the above-mentioned method for preparing the composite antibacterial film-forming liquid, in step (2), the amount of the eutectic solvent added is 20%-40% of the mass of the chitosan, and the amount of glycerol added is 20%-50% of the mass of the chitosan; in step (3), the mass-volume ratio of the Ag / ZIF-8 / g-C3N4 composite material to the total amount of the CSDG solution is 5-15 mg: 50 mL.
[0017] Furthermore, in the above-mentioned method for preparing the composite antibacterial film-forming liquid, the Ag / ZIF-8 / g-C3N4 composite material is prepared through the following steps:
[0018] 1) g-C3N4 was prepared by calcining melamine as a precursor at 500-600℃ for 3-5 h. Then, g-C3N4 was ultrasonically dispersed in methanol to obtain g-C3N4 dispersion.
[0019] 2) ZIF-8 was prepared by reacting 2-methylimidazole and zinc nitrate hexahydrate in methanol at a molar ratio of 8:1; ZIF-8 was then ultrasonically dispersed in methanol to obtain a ZIF-8 dispersion.
[0020] 3) Add the ZIF-8 dispersion from step 2) to the g-C3N4 dispersion from step 1) and mix and stir. Then add AgNO3 and continue stirring. Subsequently, add ascorbic acid and continue stirring and reacting. After solid-liquid separation and drying, the Ag / ZIF-8 / g-C3N4 is obtained.
[0021] The mass ratio of g-C3N4, ZIF-8, AgNO3 to ascorbic acid is 4:1:1.7:0.88.
[0022] Furthermore, in the above-mentioned method for preparing the composite antibacterial film-forming liquid, the eutectic solvent is prepared by mixing choline chloride and citric acid in a molar ratio of 1:1 and stirring in a water bath at 75-85°C until a colorless, transparent, and homogeneous liquid is formed.
[0023] The second technical solution provided by the present invention is a composite antibacterial film-forming liquid, which is prepared by the method described in the first technical solution.
[0024] The third technical solution provided by the present invention is an antibacterial paper, wherein the antibacterial paper is obtained by pre-treating packaging paper, soaking it in the composite antibacterial film-forming liquid described in claim 7, taking it out, spreading it out and drying it.
[0025] Furthermore, the pretreatment involves soaking the packaging paper in a 75% (v / v) ethanol solution to dewax it, rinsing it with deionized water, and drying it at 35-45°C. The soaking time is 0.5-2 hours, and the drying is done by air drying at room temperature.
[0026] The present invention provides the use of the above-mentioned antibacterial paper in food packaging materials.
[0027] This antibacterial paper utilizes the synergistic effect of the components in the composite material to give it excellent antibacterial activity, barrier properties, and UV shielding capabilities, effectively extending the shelf life of food.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The present invention uses a low eutectic solvent and glycerol as a synergistic plasticizing system, which can effectively weaken the strong hydrogen bond between chitosan molecular chains. While improving the defects of high brittleness and insufficient toughness of pure chitosan film formation, it avoids the problems of increased film water solubility and decreased moisture resistance caused by single plasticizer modification. The resulting composite antibacterial paper has both excellent mechanical toughness and water vapor barrier properties, making it suitable for packaging scenarios of high-humidity fresh food.
[0030] (2) The present invention uses Ag / ZIF-8 / g-C3N4 composite material as functional antibacterial filler. Through the contact sterilization of Ag nanoparticles and the slow-release antibacterial effect of silver ions, combined with the visible light catalytic sterilization effect of g-C3N4, and further supplemented by the stable loading and slow release of active components by the porous structure of ZIF-8, the three synergistically endow the composite antibacterial paper with excellent and long-lasting broad-spectrum antibacterial properties, which can effectively inhibit the growth and reproduction of common foodborne pathogens on the surface of fresh food.
[0031] (3) The introduction of Ag / ZIF-8 / g-C3N4 composite material of the present invention can effectively reduce the surface energy of composite antibacterial paper, give it good hydrophobic properties, reduce the adhesion residue of food juice and organic stains on the surface of packaging paper, and at the same time, under light conditions, it can catalytically degrade adsorbed organic pollutants, realize the anti-fouling and self-cleaning function, and further reduce the risk of microbial growth.
[0032] (4) The composite antibacterial paper prepared by the present invention has excellent ultraviolet shielding function, which can block the oxidation and browning of food and the degradation and deterioration of nutrients caused by ultraviolet rays in the environment. At the same time, it can maintain a suitable air permeability and humidity environment inside the packaging, slow down the loss of moisture and excessive respiration of fresh food, and effectively extend the shelf life of fresh fruits, vegetables and meat.
[0033] (5) All raw materials used in this invention are green, environmentally friendly and biodegradable materials. The amount of Ag / ZIF-8 / g-C3N4 functional filler added is low. The preparation process is mild and does not require special processes such as high temperature and high pressure. The resulting composite antibacterial paper has good biocompatibility and meets the safety requirements of food contact packaging. The process is simple to operate and suitable for industrial-scale production. It has good application prospects in the field of fresh food preservation packaging. Attached Figure Description
[0034] Figure 1 This is the XRD pattern of the thin film sample;
[0035] Figure 2 This is the infrared spectrum of the thin film sample;
[0036] Figure 3 This is a graph showing the UV transmittance of a thin film sample.
[0037] Figure 4 These are photographs of the appearance of the thin film sample;
[0038] Figure 5 This is a test graph showing the suspension stability of the film-forming solution used to prepare the thin film;
[0039] Figure 6 These are test graphs showing the water content, water solubility, and swelling degree of the thin film sample.
[0040] Figure 7 These are test results for the toughness and load-bearing capacity of the thin film sample.
[0041] Figure 8 This is a contact angle test diagram of a thin film sample;
[0042] Figure 9 This is a contact angle test diagram of a sugarcane-based antibacterial paper sample;
[0043] Figure 10 This is a test diagram showing the antifouling effect of sugarcane-based antibacterial paper samples on methylene blue aqueous solution;
[0044] Figure 11 This is a test diagram showing the adhesion of sugarcane-based antibacterial paper samples to Bacillus subtilis;
[0045] Figure 12 This is a test diagram showing the adhesion of sugarcane-based antibacterial paper samples to Stenotrophomonas maltophilia.
[0046] Figure 13 This is a test graph showing the inhibitory effect of the film-forming solution used to prepare the film on Bacillus subtilis;
[0047] Figure 14 This is a test diagram showing the inhibitory effect of the film-forming solution used to prepare the film on Stenotrophomonas maltophilia.
[0048] Figure 15 This is a test chart showing the preservation effect of sugarcane-based antibacterial paper on pork at room temperature;
[0049] Figure 16 This is a test chart showing the preservation effect of sugarcane-based antibacterial paper on pork at 4°C;
[0050] Figure 17 This is a test chart showing the preservation effect of sugarcane-based antibacterial paper on grapes at room temperature;
[0051] Figure 18 This is a test chart showing the grape preservation effect of sugarcane-based antibacterial paper at 4°C;
[0052] Figure 19 This is a graph showing the hemolysis of red blood cells in a thin film sample.
[0053] Figure 20 This is a test chart of red blood cell hemolysis on sugarcane-based antibacterial paper.
[0054] Figure 21 This is a diagram showing the soil degradation effect of sugarcane-based antibacterial paper. Detailed Implementation
[0055] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0056] The reagents required for the following examples are shown in Table 1:
[0057] Table 1. Reagents required for the experiment
[0058] Chitosan Deacetylation degree ≥ 90% Shanghai McLean Biochemical Technology Co., Ltd. choline chloride Analytical Pure Shanghai McLean Biochemical Technology Co., Ltd. Citric acid Analytical Pure Xilong Scientific Co., Ltd. Glycerol Analytical Pure Chengdu Kelong Chemical Co., Ltd. Acetic acid Analytical Pure Xilong Scientific Co., Ltd. 2-Methylimidazole Analytical Pure Aladdin Biochemical Technology Co., Ltd. Zinc nitrate hexahydrate Analytical Pure Sinopharm Chemical Reagent Co., Ltd. melamine Analytical Pure Aladdin Biochemical Technology Co., Ltd. silver nitrate Analytical Pure Sinopharm Chemical Reagent Co., Ltd. Citric acid Analytical Pure Sinopharm Chemical Reagent Co., Ltd. ascorbic acid Analytical Pure Sinopharm Chemical Reagent Co., Ltd. methanol Analytical Pure Xilong Scientific Co., Ltd. Methylene blue Analytical Pure Sinopharm Chemical Reagent Co., Ltd. Triton Analytical Pure Beijing Solarbio Technology Co., Ltd. Agar powder Analytical Pure Sinopharm Chemical Reagent Co., Ltd. Sodium chloride Analytical Pure Sinopharm Chemical Reagent Co., Ltd. Yeast extract Analytical Pure UK Oakold Ltd. trypsin Analytical Pure UK Oakold Ltd.
[0059] Example 1
[0060] The composite antibacterial film-forming liquid provided in this embodiment is prepared sequentially through the following steps:
[0061] 1) Weigh 0.75 g of chitosan (CS), add 50 mL of 0.5% (v / v) glacial acetic acid aqueous solution, stir at 40℃ and 800 r / min for 6 h until completely dissolved, let stand for 30 min to remove bubbles, and set aside.
[0062] 2) Add 0.225 g of eutectic solvent (DES) to step 1), stir at room temperature for 1 h, then add 0.15 g of glycerol and continue stirring for 1 h until the solution is uniform and transparent, and record it as CSDG solution.
[0063] 3) Weigh 5 mg of AZC powder, add 10 mL of CSDG solution, and sonicate for 60 min until there is no obvious agglomeration. Then add 40 mL of CSDG solution and stir at room temperature for 2 h to ensure that the system is uniform and there are no obvious large particles. The resulting mixture is called CSDGA-5 film-forming solution.
[0064] Wherein: the eutectic solvent (DES) mentioned in step 1) is prepared by the following method: accurately weigh choline chloride (ChCl) and citric acid (CA) in a molar ratio of 1:1, mix them, and place them in an 80°C water bath with continuous magnetic stirring until a colorless, transparent, and homogeneous liquid is formed. Cool to room temperature, seal and dry for storage, and use later.
[0065] Step 3) The AZC composite material is prepared by the following steps:
[0066] (1) Preparation of g-C3N4
[0067] Using melamine as a precursor, 5 g of melamine was added to a 50 mL crucible and heated to 550 °C in a muffle furnace at a heating rate of 5 °C / min. The mixture was then calcined for 4 h and ground into fine particles for later use.
[0068] (2) Preparation of ZIF-8 powder
[0069] 13.2 g of 2-methylimidazole was ultrasonically dispersed in 70 mL of methanol to obtain a 2-methylimidazole methanol solution, and 5.94 g of zinc nitrate hexahydrate was ultrasonically dispersed in 30 mL of methanol to obtain a zinc nitrate hexahydrate methanol solution. The zinc nitrate hexahydrate methanol solution was added to the 2-methylimidazole methanol solution, and the mixture was stirred for 3 h to ensure complete reaction. The resulting solution was filtered under reduced pressure, dried at 60 °C overnight, and ground to obtain ZIF-8 powder for later use.
[0070] (3) G-C3N4 (0.4 g) was ultrasonically dispersed in 80 mL of methanol solution to obtain g-C3N4 methanol solution. ZIF-8 (0.1 g) was ultrasonically dispersed in 20 mL of methanol solution to obtain ZIF-8 methanol solution. Then, ZIF-8 methanol solution was added to g-C3N4 methanol solution and mixed and stirred for 30 min. AgNO3 (1 mmol) was added and stirring was continued for 1.5 h. Ascorbic acid (0.5 mmol) was added and stirring was continued for 2 h. The mixture was filtered under reduced pressure and dried at 60 °C to obtain Ag / ZIF-8 / g-C3N4 (denoted as AZC) composite material, which was then ground for later use.
[0071] Example 2
[0072] Another composite antibacterial film-forming liquid provided in this embodiment has basically the same preparation steps and parameters as in Example 1. The only difference is: Step 3) Weigh 10 mg of AZC powder, add 10 mL of CSDG solution, ultrasonically disperse for 60 min until there is no obvious agglomeration, then add 40 mL of CSDG solution and stir at room temperature for 2 h to ensure that the system is uniform and there are no obvious large particles to obtain a mixed liquid, which is called CSDGA-10 film-forming liquid.
[0073] Example 3
[0074] Another composite antibacterial film-forming liquid provided in this embodiment has basically the same preparation steps and parameters as in Example 1. The only difference is: Step 3) Weigh 15 mg of AZC powder, add 10 mL of CSDG solution, ultrasonically disperse for 60 min until there is no obvious agglomeration, then add 40 mL of CSDG solution and stir at room temperature for 2 h to ensure that the system is uniform and there are no obvious large particles to obtain a mixed liquid, which is called CSDGA-15 film-forming liquid.
[0075] Example 4
[0076] Another composite antibacterial film-forming liquid provided in this embodiment has basically the same preparation steps and parameters as in Example 1. The only difference is that in step 1), 0.5 g of chitosan (CS) is weighed, 50 mL of 0.5% (v / v) glacial acetic acid aqueous solution is added, and the mixture is stirred at 40℃ and 800 r / min for 6 h until completely dissolved. The mixture is then allowed to stand for 30 min to remove bubbles before use.
[0077] Example 5
[0078] Another composite antibacterial film-forming liquid provided in this embodiment has basically the same preparation steps and parameters as in Example 1. The only difference is that in step 1), 1.0 g of chitosan (CS) is weighed, 50 mL of 0.5% (v / v) glacial acetic acid aqueous solution is added, and the mixture is stirred at 40℃ and 800 r / min for 6 h until completely dissolved. The mixture is then allowed to stand for 30 min to remove bubbles before use.
[0079] Example 6
[0080] Another composite antibacterial film-forming liquid provided in this embodiment has basically the same preparation steps and parameters as in Example 1. The only difference is that in step 2), 0.15 g of DES solution is added to step 1), stirred at room temperature for 1 h, and then 0.15 g of glycerol is added and stirred for 1 h until the solution is uniform and transparent.
[0081] Example 7
[0082] Another composite antibacterial film-forming liquid provided in this embodiment has basically the same preparation steps and parameters as in Example 1. The only difference is that in step 2), 0.3 g of DES solution is added to step 1), and after stirring at room temperature for 1 h, 0.15 g of glycerol is added and stirred for 1 h until the solution is uniform and transparent.
[0083] Example 8
[0084] Another composite antibacterial film-forming liquid provided in this embodiment has basically the same preparation steps and parameters as in Example 1. The only difference is that in step 2), 0.225 g of DES solution is added to step 1), and after stirring at room temperature for 1 h, 0.3 g of glycerol is added and stirred for 1 h until the solution is uniform and transparent.
[0085] Example 9
[0086] Another composite antibacterial film-forming liquid provided in this embodiment has basically the same preparation steps and parameters as in Example 1. The only difference is that in step 2), 0.225 g of DES solution is added to step 1), and after stirring at room temperature for 1 h, 0.375 g of glycerol is added and stirred for 1 h until the solution is uniform and transparent.
[0087] Application Example 1
[0088] This application example provides a sugarcane antibacterial paper. Purchased sugarcane paper is cut into 10×10 cm pieces, soaked in a 75% (v / v) ethanol solution to dewax, thoroughly rinsed with deionized water, and dried at 40°C for later use. The treated sugarcane paper is then soaked in the uniformly dispersed composite antibacterial film-forming solution prepared in Example 1 for 1 hour. It is then removed, laid flat, and allowed to air dry naturally at room temperature. This is designated as S-CSDGA-5 antibacterial paper.
[0089] Application Example 2
[0090] This application example provides an antibacterial sugarcane paper. Purchased sugarcane paper is cut into 10×10 cm pieces, soaked in a 75% (v / v) ethanol solution to dewax, thoroughly rinsed with deionized water, and dried at 40°C for later use. The treated sugarcane paper is then soaked in the uniformly dispersed composite antibacterial film-forming solution prepared in Example 2 for 1 hour. Afterward, it is removed, laid flat, and allowed to air dry naturally at room temperature. This is designated as S-CSDGA-10 antibacterial paper.
[0091] Application Example 3
[0092] This application example provides an antibacterial sugarcane paper. Purchased sugarcane paper is cut into 10×10 cm pieces, soaked in a 75% (v / v) ethanol solution to dewax, thoroughly rinsed with deionized water, and dried at 40°C for later use. The treated sugarcane paper is then soaked in the uniformly dispersed composite antibacterial film-forming solution prepared in Example 3 for 1 hour. Afterward, it is removed, laid flat, and allowed to air dry naturally at room temperature. This is designated as S-CSDGA-15 antibacterial paper.
[0093] Comparative Example 1
[0094] This comparative example provides a CS antibacterial film-forming liquid, the preparation method of which is as follows:
[0095] 1) Weigh 0.75 g of chitosan (CS), add 50 mL of 0.5% (v / v) glacial acetic acid aqueous solution, stir at 40℃ and 800 r / min for 6 h until completely dissolved, let stand for 30 min to remove bubbles, and record as CS antibacterial film-forming solution.
[0096] Comparative Example 2
[0097] This comparative example provides a CSD antibacterial film-forming liquid, the preparation method of which is as follows:
[0098] 1) Weigh 0.75 g of chitosan (CS), add 50 mL of 0.5% (v / v) glacial acetic acid aqueous solution, stir at 40℃ and 800 r / min for 6 h until completely dissolved, let stand for 30 min to remove bubbles, and set aside.
[0099] 2) Add 0.225 g of DES solution to step 1), stir at room temperature for 1 h, and set aside as CSD antibacterial film-forming solution.
[0100] Comparative Example 3
[0101] This comparative example provides a CSG antibacterial film-forming solution, the preparation method of which is as follows:
[0102] 1) Weigh 0.75 g of chitosan (CS), add 50 mL of 0.5% (v / v) glacial acetic acid aqueous solution, stir at 40℃ and 800 r / min for 6 h until completely dissolved, let stand for 30 min to remove bubbles, and set aside.
[0103] 2) Add 0.15 g of glycerol solution to step 1), stir at room temperature for 1 h and set aside for later use. This solution is called CSG antibacterial film-forming solution.
[0104] Comparative Example 4
[0105] This comparative example provides a CSDG antibacterial film-forming solution, the preparation method of which is as follows:
[0106] 1) Weigh 0.75 g of chitosan (CS), add 50 mL of 0.5% (v / v) glacial acetic acid aqueous solution, stir at 40℃ and 800 r / min for 6 h until completely dissolved, let stand for 30 min to remove bubbles, and set aside.
[0107] 2) Add 0.225 g of DES solution to step 1), stir at room temperature for 1 h, then add 0.15 g of glycerol and continue stirring for 1 h until the solution is uniform and transparent. This solution is called CSDG solution.
[0108] Comparative Application Example 1
[0109] This comparative example provides an S-CS antibacterial paper, which is prepared as follows: Purchased sugarcane paper is cut into 10×10 cm pieces, soaked in a 75% ethanol solution to dewax, thoroughly rinsed with deionized water, and dried at 40°C. The treated sugarcane paper is then soaked in the well-dispersed CS antibacterial film-forming solution prepared in Comparative Example 1 for 1 hour, removed, flattened, and allowed to air dry at room temperature. This is designated as S-CS antibacterial paper.
[0110] Comparative Application Example 2
[0111] This comparative example provides an S-CSD antibacterial paper, which is prepared as follows: Purchased sugarcane paper is cut into 10×10cm pieces, soaked in a 75% ethanol solution to dewax, thoroughly rinsed with deionized water, and dried at 40℃. The treated sugarcane paper is then soaked in the uniformly dispersed CSD prepared in Comparative Example 2 for 1 hour, removed, flattened, and allowed to air dry at room temperature. This is designated as S-CSD antibacterial paper.
[0112] Comparative Application Example 3
[0113] This comparative example provides an S-CSG antibacterial paper, prepared as follows: Purchased sugarcane paper is cut into 10×10cm pieces, soaked in a 75% ethanol solution for dewaxing, thoroughly rinsed with deionized water, and dried at 40℃. The treated sugarcane paper is then soaked in the well-dispersed CSG film-forming solution prepared in Comparative Example 3 for 1 hour, removed, flattened, and allowed to air dry at room temperature; this is designated as S-CSG antibacterial paper.
[0114] Comparative Application Example 4
[0115] This comparative example provides an S-CSDG antibacterial paper, prepared as follows: Purchased sugarcane paper is cut into 10×10cm pieces, soaked in a 75% ethanol solution for dewaxing, thoroughly rinsed with deionized water, and dried at 40℃. The treated sugarcane paper is then soaked in the well-dispersed CSDG film-forming solution prepared in Comparative Example 4 for 1 hour, removed, flattened, and allowed to air dry at room temperature; this is designated as S-CSDG antibacterial paper.
[0116] To verify the performance of the technical solution provided in this application, the membrane performance test is given below.
[0117] For ease of testing, 10 mL of the mixture obtained in step 3) of Example 1 was slowly poured into a clean, dry φ90 mm petri dish. The mixture was allowed to stand at room temperature for 48 h to allow the solvent to evaporate naturally. Then, it was transferred to a 40°C oven and dried for 6 h until the membrane was completely dry. The dried membrane was then immersed in a 2% (w / v) NaOH solution for 30 min to neutralize residual acetic acid. It was then rinsed with deionized water until neutral and air-dried at room temperature for later use. The synthesized membrane was designated CSDGA-5.
[0118] Take 10 mL of the mixture obtained in step 3) of Example 2 and slowly pour it into a clean, dry φ90 mm petri dish. Let it stand at room temperature for 48 h to allow the solvent to evaporate naturally. Then, transfer it to a 40℃ oven and dry for 6 h until the membrane is completely dry. Next, immerse the dry membrane in a 2% (w / v) NaOH solution for 30 min to neutralize the residual acetic acid. Then, rinse it with deionized water until neutral and air dry it at room temperature for later use. The synthesized membrane is designated as CSDGA-10.
[0119] Take 10 mL of the mixture obtained in step 3) of Example 3 and slowly pour it into a clean, dry φ90 mm petri dish. Let it stand at room temperature for 48 h to allow the solvent to evaporate naturally. Then, transfer it to a 40℃ oven and dry for 6 h until the membrane is completely dry. Next, immerse the dry membrane in a 2% (w / v) NaOH solution for 30 min to neutralize the residual acetic acid. Then, rinse it with deionized water until neutral and air dry it at room temperature for later use. The synthesized membrane is designated as CSDGA-15.
[0120] Using the same parameters, the CS, CSD, CSG, and CSDG film-forming solutions were slowly mixed and poured into clean, dry φ90 mm petri dishes. The solutions were allowed to stand at room temperature for 48 h to allow the solvent to evaporate naturally, then transferred to a 40℃ oven for 6 h to dry completely. The dried films were then immersed in a 2% (w / v) NaOH solution for 30 min to neutralize residual acetic acid, rinsed with deionized water until neutral, and air-dried at room temperature for later use. The resulting films were designated as CS, CSD, CSG, and CSDG, respectively.
[0121] I. Material Characterization
[0122] The crystal structure of the prepared thin films was analyzed using a Bruker D8 powder X-ray diffractometry (PXRD) system with Cu Kα as the radiation source, a tube voltage of 40 kV, a current of 30 mA, and a scanning range of 5–90°. Functional group analysis of the prepared samples was performed using a NICOLET 380 Fourier Transform Infrared Spectrometer (FT-IR) with a wavelength range of 400 cm⁻¹. -1 -4000cm -1 The ultraviolet transmittance of the prepared thin film was tested using a TU-1901 UV-Vis spectrophotometer. The entire test was conducted at room temperature, with the test wavelength scanning range set to 200–800 nm. A blank quartz plate was used as a reference calibration baseline.
[0123] 1. XRD inspection
[0124] The XRD patterns of the CSDGA-5, CSDGA-10, and CSDGA-15 films prepared by the film-forming solutions in Examples 1-3, and the CS, CSD, CSG, and CSDG films prepared by the film-forming solutions in Comparative Examples 1-4 are shown below. Figure 1 As shown, clear crystalline peaks are present at 2θ = 11° and 21°, with relatively sharp peak shapes, indicating that CS itself has a semi-crystalline structure. The addition of the eutectic solvent (DES) disrupts the hydrogen bonds between CS molecular chains, leading to a decrease in crystallinity. Glycerol, as a small-molecule plasticizer, inserts into the spaces between CS molecular chains, increasing the interchain spacing, disrupting the crystalline regions, and making the material more amorphous. The characteristic peak positions of CS did not shift significantly after the addition of Ag / ZIF-8 / g-C3N4 nanomaterials, indicating that the addition of Ag / ZIF-8 / g-C3N4 did not change the interplanar spacing of CS and did not form new chemical bonds; it was mainly a physical recombination. Because the Ag / ZIF-8 / g-C3N4 nanoparticles are highly dispersed in the CS matrix without significant agglomeration, they cannot form ordered crystal diffraction signals detectable by XRD.
[0125] 2. Infrared spectrum
[0126] The infrared spectra of the CSDGA-5, CSDGA-10, and CSDGA-15 films obtained from the film-forming solutions prepared in Examples 1-3, and the CS, CSD, CSG, and CSDG films prepared from the film-forming solutions prepared in Comparative Examples 1-4 are shown below. Figure 2 As shown, 3200-3400 cm -1 It is the stretching vibration of OH and NH, 2900-2930 cm. -1 For CH stretching vibration, 1562 cm -1 It is an NH bending vibration, 1394 cm. -1 It is CH bending vibration, 1028 cm -1 It is the CO stretching vibration in the sugar ring, 883 cm. -1 It is an out-of-plane bending vibration of the CH group in the sugar ring. After adding DES and glycerol, the chromatogram was 1562 cm⁻¹. -1 The NH peak at 1028 cm⁻¹ -1 The CO peak of the sugar ring at 3200-3400 cm⁻¹ was significantly weakened and its shape became blunt, indicating that DES and CS underwent an acid-base interaction, consuming the free amino group. DES disrupted the hydrogen bonds between the molecular chains of CS, weakening the ordered arrangement of the sugar ring. -1 The OH and NH peaks broadened significantly and shifted to lower wavenumbers, indicating that the hydroxyl groups of glycerol formed new hydrogen bonds with CS, thus plasticizing the molecular chain. The addition of Ag / ZIF-8 / g-C3N4 did not produce any new peaks, indicating that the nanoparticles were highly dispersed in the matrix without significant aggregation, and their characteristic vibrations were masked by the strong signal from the matrix.
[0127] 3. Ultraviolet transmittance
[0128] The CSDGA-5, CSDGA-10, and CSDGA-15 films obtained from the film-forming solutions prepared in Examples 1-3, and the CS, CSD, CSG, and CSDG films prepared from the film-forming solutions in Comparative Examples 1-4, can be directly analyzed for their UV transmittance, allowing for a direct assessment of the film samples' ability to block ultraviolet light. Figure 3 As shown, pure CS has a semi-crystalline structure, resulting in less scattering of visible light and the best light transmittance. Glycerin, acting as a plasticizer, inserts into the CS molecular chains, slightly disrupting the crystalline regions, but without introducing a strong scattering source. Therefore, the decrease in transmittance is minimal, maintaining good transparency. DES interacts with the amino groups of CS, disrupting the ordered arrangement of the molecular chains. Simultaneously, the introduction of DES increases the amorphous nature of the material, enhancing visible light scattering and leading to a significant decrease in transmittance. When Ag / ZIF-8 / g-C3N4 is dispersed in the CSDG matrix, it scatters incident light. The higher the amount added, the more scattering centers there are, resulting in stronger scattering of visible light and lower transmittance. The lower the UV transmittance of the film, the better its resistance to UV oxidation, effectively inhibiting UV-induced lipid oxidation, pigment degradation, and quality deterioration in food. This is a significant advantage for food preservation and packaging materials.
[0129] II. Membrane Performance Testing
[0130] 1. Images of the thin film's appearance
[0131] from Figure 4 As can be seen from the images of the films, the CSDGA-5, CSDGA-10, and CSDGA-15 films prepared by the film-forming solutions of Examples 1-3 differ in color and transparency from the CS, CSD, CSG, and CSDG films prepared by the film-forming solutions of Comparative Examples 1-4. Compared to the films prepared by Comparative Examples 1-4, after the addition of Ag / ZIF-8 / g-C3N4 nanomaterials, the films prepared by Examples 1-3 showed reduced transparency, increased roughness, and gradually darkened color, indicating that the filler was uniformly dispersed in the matrix.
[0132] 2. Basic physical properties
[0133] Stability: such as Figure 5 As shown, the film-forming solutions prepared in Examples 1-3 and the CS, CSD, CSG, and CSDG film-forming solutions prepared in Comparative Examples 1-4 did not show obvious particle deposition after being placed under natural conditions for 7 days. This indicates that the added DES, Ag / ZIF-8 / g-C3N4 nanoparticles and glycerol are uniformly dispersed in the CS substrate solution and have a certain suspension stability.
[0134] The water resistance of the film samples was evaluated using water content, water solubility, and swelling degree. The specific test methods are as follows:
[0135] Moisture content: After drying to equilibrium, the film sample was cut into 2 cm × 2 cm pieces, and the initial mass (M0) was accurately weighed. The sample was then placed in a 105℃ oven for constant drying until constant weight. After cooling to room temperature, the sample mass was weighed again (M1). The moisture content of the film was calculated based on the mass loss using the following formula:
[0136] (1)
[0137] Water solubility: Take a film sample dried to constant weight, accurately weigh the initial mass (M0), immerse it in deionized water at 25℃, and let it stand at a constant temperature for 24 h to allow the film to fully dissolve and reach equilibrium. Remove the remaining insoluble film, place it in an oven at 105℃ to dry to constant weight, and weigh the remaining solid mass (M2). Calculate the film water solubility:
[0138] (2)
[0139] Swelling degree: Weigh the initial mass of the dried film (M0), completely immerse the sample in deionized water at 25℃, and soak at this temperature for 24 hours to reach swelling equilibrium. Quickly blot the free moisture from the film surface with filter paper, and accurately weigh the wet weight of the swollen film (M3). Swelling degree calculation formula:
[0140] (3)
[0141] like Figure 6 As shown, Comparative Examples 1-4 exhibit higher water content, water solubility, and swelling degree, while Examples 1-3 show varying degrees of reduction in water content, water solubility, and swelling degree compared to Comparative Examples 1-4. This is attributed to the addition of DES and glycerol, which improve the water-responsive physicochemical properties of the chitosan matrix, weaken the interaction between chitosan molecular chains and water molecules, and reduce the system's water absorption and dissolution characteristics. The CSDG film obtained by combining these two components exhibits water-sensitive properties between CS, CSD, and CSG, achieving a compromise in water-responsive characteristics. Introducing Ag / ZIF-8 / g-C3N4 composite nanomaterials into the CSDG solution fills the internal pore structure of the membrane, reducing the penetration and binding of water molecules into the membrane matrix, effectively improving the water resistance stability of the chitosan-based film in an aqueous environment. This provides a reliable basis for the practical application of this composite film in the field of fresh food preservation packaging in an aqueous environment.
[0142] 2. Mechanical properties
[0143] The flexibility and mechanical load-bearing capacity of each group of chitosan-based films were visually evaluated through curling, torsional deformation tests, and weight suspension load tests. The specific test methods are as follows:
[0144] Toughness: The film was uniformly cut into standard rectangular strips of 1 cm × 10 cm. The film was repeatedly rolled and bent, and the toughness of the film was evaluated by observing whether cracks, brittle fractures or other damage occurred.
[0145] Load-bearing capacity: A rectangular film of 1 cm × 10 cm continuously bears a standard weight of 200 g. The deformation and damage of the film are observed to visually evaluate the load-bearing capacity of the film.
[0146] like Figure 7 As shown, the CSDGA-5, CSDGA-10, and CSDGA-15 films prepared by the film-forming solutions in Examples 1-3, and the CS, CSD, CSG, and CSDG films prepared by the film-forming solutions in Comparative Examples 1-4, can all complete the curling and torsional deformation operations, and can stably bear a 200 g load without fracture failure. Due to the high density of intermolecular hydrogen bonds in the pure CS film, the material has strong rigidity. Comparative Example 1 is prone to stress creases during deformation. In Comparative Examples 2-4, the introduction of glycerol and DES can improve the flexibility of the film by weakening the intermolecular forces of chitosan. The toughness and load-bearing capacity results of Examples 1-3 show that the introduction of Ag / ZIF-8 / g-C3N4 nanomaterials did not degrade the inherent flexibility of the chitosan matrix, and could improve the processing and bending adaptability and mechanical structural stability of the composite film, meeting the actual use requirements of flexible food packaging films.
[0147] 3. Static water contact angle
[0148] The water contact angle (WCA) is the angle between the tangent at the gas-liquid interface and the solid-liquid interface when a droplet is stationary on a thin film surface. It is used to measure the hydrophilicity or hydrophobicity of a sample. A WCA < 90° indicates hydrophilicity; a WCA > 90° indicates hydrophobicity; and a WCA > 150° indicates superhydrophobicity. The water contact angle (WCA) is measured using an SDC-200 contact angle meter. A flat, wrinkle-free, and undamaged thin film sample is fixed on the test stage. 2 μL of deionized water is drawn up using a microsyringe and slowly added to the flat surface of the film. After the droplet stabilizes, its profile is photographed, and the static water contact angle (WCA) is calculated using a fitting method.
[0149] like Figure 8As shown, the CSDGA-5, CSDGA-10, and CSDGA-15 films prepared with the film-forming solutions of Examples 1-3, and the CS, CSD, CSG, and CSDG films prepared with the film-forming solutions of Comparative Examples 1-4, have water contact angles of 97.890°, 95.008°, 91.905°, 87.451°, 92.043°, 93.397°, and 91.944°, respectively. The CS film exhibits slight hydrophobicity. The contact angle decreases slightly after the introduction of DES and glycerol, respectively. When DES and glycerol are both added, the contact angle decreases significantly. This is because the large number of hydroxyl and polar groups in glycerol and DES increases the surface polarity of the film and enhances the wetting ability of water molecules. After gradient doping of Ag / ZIF-8 / g-C3N4 nanoparticles into the CSDG substrate, the overall contact angle of the film showed a slight upward trend. This indicates that the nanoparticles can improve the hydrophobicity of the film by changing the micro-roughness of the film surface and filling the polymer pore structure, which helps to block water penetration and improve the stability of the film in humid environments.
[0150] like Figure 9 As shown, the contact angle of the original sugarcane paper is only 88.930°. In comparison, the water contact angles of the antibacterial papers S-CS, S-CSD, S-CSG, S-CSDG, S-CSDGA-5, S-CSDGA-10, and S-CSDGA-15 prepared in Application Examples 1-3 and 1-4 are 89.308°, 90.437°, 89.910°, 90.232°, 95.577°, 95.606°, and 95.535°, respectively. The original sugarcane paper has a porous fibrous structure and is easily wetted by water. The contact angles of the antibacterial papers coated with various chitosan coatings are all higher than those of the original sugarcane paper, indicating that the chitosan coatings effectively seal the pores on the sugarcane fiber surface and improve the wettability of the substrate. Compared to the pure film sample, the contact angle was higher overall after the same formulation was coated on sugarcane paper substrate. This is attributed to the rough substrate effect brought by the sugarcane fiber substrate. According to the Wenzel wetting model, the substrate roughness will amplify the hydrophobic properties of the material itself.
[0151] 4. Investigation into anti-fouling and self-cleaning abilities
[0152] Antibacterial paper was fixed at an angle, and a quantitative amount of 1 mol / L methylene blue aqueous solution was evenly dripped onto the film surface. The spreading and adhesion of pollutants were observed, and the amount of residue on the film surface was recorded. Subsequently, a small amount of deionized water was used to rinse the film surface, and the cleaning effect of the water flow on the stains was observed. By comparing the degree of residue on the film surface before and after rinsing, the antifouling performance and self-cleaning properties of the film were evaluated.
[0153] like Figure 10As shown, when methylene blue solution drips onto sugarcane paper without a film-forming solution, it leaves marks on the surface. In Application Examples 1-3, compared to Application Examples 1-4, the antibacterial papers S-CS, S-CSD, S-CSG, S-CSDG, S-CSDGA-5, S-CSDGA-10, and S-CSDGA-15 show varying degrees of improved antifouling ability. In Application Examples 1-3, due to the simultaneous addition of glycerol, DES, and Ag / ZIF-8 / g-C3N4 nanomaterials, methylene blue droplets barely wet the surface. When the prepared antibacterial papers are immersed in an aqueous methylene blue solution, the sugarcane paper without the film-forming solution is completely stained and shows significant color loss after immersion in water. The antibacterial papers coated with the film-forming solution show varying degrees of staining, but the degree of staining is lower than that of the uncoated sugarcane paper. Immersion in water results in slight color loss. This indicates that the prepared antibacterial papers possess varying degrees of antifouling and self-cleaning capabilities.
[0154] 5. Investigation into antibacterial properties
[0155] Antibacterial adhesion ability: Antibacterial papers prepared in Application Examples 1-3 and Comparative Application Examples 1-4, including S-CS, S-CSD, S-CSG, S-CSDG, S-CSDGA-5, S-CSDGA-10, and S-CSDGA-15, were sterilized by UV exposure and then immersed in a solution of 10% concentration. 6 The antibacterial paper was incubated with CFU / mL of Bacillus subtilis and Stenotrophomonas maltophilia at 37°C for 4 h to allow for sufficient bacterial adhesion. After incubation, the antibacterial paper was removed and gently rinsed three times with sterile PBS buffer to remove any unadhered free bacteria. The rinsed antibacterial paper was then placed in a sterile centrifuge tube, and the same amount of PBS buffer was added and vortexed to elute the adhered bacteria. After serial dilution, the mixture was spread onto solid culture medium and incubated at 37°C for 12 h. The plates were then photographed to record the experimental results, thereby evaluating the antibacterial adhesion performance of the samples. Figure 11 , Figure 12As shown, the blank sugarcane paper fibers are loose and porous, making them highly susceptible to bacterial adsorption. Both *Bacillus subtilis* and *Stenotrophomonas maltophilia* produced numerous colonies on the plate, indicating that the virgin sugarcane paper has a strong adhesive ability to bacteria. In contrast, the S-CS sample prepared using Example 1, coated only with pure chitosan, showed only a slight decrease in colony count compared to the original paper. The S-CDS, S-CSG, and S-CSDG samples prepared by introducing DES and glycerol showed a certain degree of decrease in colony density because the coating blocked the porous structure of the sugarcane paper, reducing the physical trapping and adsorption of bacteria through the fiber gaps. When Ag / ZIF-8 / g-C3N4 nanomaterials were introduced into the CSDG system, the number of colonies adhering to the antibacterial papers prepared in Examples 1-3 was significantly reduced. The results above indicate that the modified coating improves the hydrophobicity of the sugarcane paper surface. The hydrophobic interface can weaken the spreading and retention of the solution on the surface, thereby reducing the colonization and adhesion of bacteria on the paper surface from a physical perspective. This can effectively reduce the amount of microorganisms attached to the packaging surface and reduce the risk of food being contaminated by microorganisms on the contact surface.
[0156] Antibacterial activity: The inhibition zone method was used to evaluate the antibacterial effects of the film-forming solutions CS, CSD, CSG, CSDG, CSDGA-5, CSDGA-10, and CSDGA-15 prepared in Examples 1-3 and Comparative Examples 1-4. *Bacillus subtilis* and *Stenotrophomonas maltophilia* bacterial suspensions were evenly spread on the surface of solid LB agar. A 5mm diameter hole was punched in the center of the agar using a sterile punch, and 100 µL of the prepared composite film-forming solution was added to each hole. Sterile pure water was used as a blank control. All agar plates were incubated at 37℃ for 24 h, and photographs were taken to record the results. The size of the inhibition zone was used to visually evaluate the inhibitory effect of the film-forming solution on the two bacteria. Results are as follows: Figure 13 , Figure 14 As shown, the blank control group showed no significant inhibition zone against Bacillus subtilis and Stenotrophomonas maltophilia, while the CS film-forming solution formed a weak inhibition zone. The diameter of the inhibition zone increased to varying degrees after the introduction of DES, glycerol, and Ag / ZIF-8 / g-C3N4 nanomaterials. This may be because the protonated amino groups in chitosan molecules can bind to negatively charged phospholipid components on the bacterial cell membrane surface, disrupting cell membrane integrity and causing intracellular leakage. Glycerol can improve the dispersibility of chitosan molecules, enhance the contact efficiency between active groups and bacteria, and synergistically strengthen the inherent antibacterial ability of chitosan. The addition of Ag / ZIF-8 / g-C3N4 nanomaterials, due to the slow release of silver and zinc ions, forms a synergistic antibacterial system with chitosan, enhancing the antibacterial ability of the film-forming solution.
[0157] Combining bacterial adhesion experiments and film-forming liquid antibacterial experiments, it can be seen that the antibacterial paper prepared in Examples 1-3 achieves physical antibacterial adhesion through hydrophobic surface structure on the one hand, and chitosan and nanomaterials can slowly and effectively release antibacterial substances to produce chemical bactericidal effect on the other hand. The dual mechanism of physical barrier and chemical antibacterial effect gives the sugarcane-based packaging material excellent comprehensive antibacterial and quality preservation capabilities.
[0158] III. Food Preservation Experiment
[0159] Fresh pork is a high-protein, perishable animal-based food, while grapes are a high-moisture, high-sugar, perishable fruit and vegetable. By conducting storage and preservation experiments on these two typical fresh foods simultaneously at room temperature and 4°C, a comprehensive assessment of the preservation potential and practical suitability of sugarcane-based composite antibacterial packaging paper can be achieved. Pork primarily deteriorates through bacterial proliferation, protein decomposition, and lipid oxidation. Grape spoilage is induced by fungal infection, fruit respiration and water loss, and senescence and browning of the peel. The spoilage process is accompanied by the growth of putrefactive bacteria, which exacerbates fruit deterioration.
[0160] Using fresh grapes and fresh pork as experimental subjects, the preservation effects of seven antibacterial papers (S-CS, S-CSD, S-CSG, S-CSDG, S-CSDGA-5, S-CSDGA-10, and S-CSDGA-15) prepared in Examples 1-3 and Examples 1-4 were investigated and compared under low-temperature refrigeration at 4℃ and room temperature conditions. The preservation and antibacterial properties of different antibacterial papers were systematically compared by measuring the weight loss rate, pH value, and total colony count during sample storage, combined with morphological observation. A standard preservation film group and a blank group were also set up as controls. Fresh grapes without damage, mold, insect infestation, and uniform ripeness were selected. After removing surface dust, they were wiped with 75% alcohol and allowed to air dry naturally. They were then randomly grouped and prepared for use. Fresh pork was defasciated and congested, cut into uniform 30 g pieces using a sterile scalpel, and the surface blood was absorbed with sterile filter paper before use. Pretreated grape and pork samples were placed directly into plastic cups. Seven different types of antibacterial paper were placed on the rim of the cups. The control group was left exposed, while the ordinary food-grade plastic wrap group had the rim of the cups wrapped with ordinary food-grade plastic wrap. Each group was tested in triplicate.
[0161] From the start of storage, all parallel samples from each group were photographed regularly to record changes in their appearance, including wilting, browning, and mold growth on grape skins, and spoilage characteristics such as darkening, stickiness, and water seepage in pork. Simultaneously, the daily mass of each group of samples was accurately weighed using an electronic analytical balance, with the initial mass recorded as M. 0, The daily weighing is recorded as mass M. t Calculate the weight loss rate according to the formula:
[0162] (4)
[0163] A suitable amount of grape pulp was randomly selected, placed in a sterile homogenizing bag, ground and homogenized, filtered to obtain the supernatant, and the pH value of the supernatant was measured using a calibrated pH meter; a suitable amount of pork sample was taken, thoroughly chopped with sterile scissors, added with sterile PBS solution, and placed in an ultrasonic cleaner for 15 min at room temperature to complete the homogenization process, and the supernatant was obtained by centrifugation and the pH value was measured.
[0164] At regular intervals, approximately 5 g of pork sample was taken and finely chopped using sterile scissors. The sample was then placed in a sterile homogenization bag, and 10 mL of sterile PBS solution was added. The bag was then ultrasonically treated at room temperature for 15 min to ensure thorough elution and dispersion of microorganisms, thus completing sample homogenization. Subsequently, serial dilutions were performed, and the samples were plated. After incubation at 37°C for 48 h, the total viable count (TVC) was calculated using the following formula:
[0165] (5)
[0166] Where CFU is the number of colonies on the plate, D is the dilution factor, V is the plating volume, and M is the sample mass.
[0167] Comparing the effects of antibacterial papers prepared in Examples 1-3 and 1-4 (S-CS, S-CSD, S-CSG, S-CSDG, S-CSDGA-5, S-CSDGA-10, and S-CSDGA-15) on pork preservation at room temperature and 4°C, the results are as follows: Figure 15 , Figure 16As shown, under normal temperature conditions, the pork in the control group exhibited signs of spoilage, including stickiness, dark browning, and a sour, putrid odor. The pork wrapped in antibacterial paper with sugarcane paper as the base showed slightly better spoilage compared to the control group. At 4℃, the pork in the control group hardened due to accelerated surface moisture evaporation caused by the refrigerator's air-cooling circulation, resulting in a higher weight loss rate. The high porosity and strong hydrophilicity of the sugarcane paper in the control group prevented effective moisture loss, leading to a continuous increase in weight loss with prolonged storage. The composite coating sealed the internal pores of the sugarcane paper, while the moderately breathable structure prevented excessive moisture accumulation inside the packaging, significantly reducing quality loss during storage. Therefore, the pork wrapped in antibacterial paper with sugarcane paper as the base showed varying degrees of weight loss reduction. The pH value of the pork system directly reflects the degree of protein decomposition. The decomposition of proteins by putrefactive bacteria, producing amines and ammonia, causes a continuous increase in the system's pH. The pH of the pork in the control group showed a rapid upward trend under both room temperature and 4℃ low-temperature refrigeration conditions, indicating the most severe spoilage. The chitosan matrix itself can inhibit the metabolic activity of spoilage bacteria. The addition of Ag / ZIF-8 / g-C3N4 nanomaterials further enhanced the antibacterial ability, effectively slowing the accumulation of alkaline metabolites and suppressing the pH rise in pork. The 4℃ refrigeration environment further stabilized the pH of the pork system by inhibiting microbial physiological metabolism, thus extending the storage time. Total colony count (TVC) is one of the indicators for evaluating the hygienic quality of pork. The blank sugarcane paper could not prevent microorganisms from attaching and multiplying on the meat surface. In the later stages of storage, the total colony count far exceeded the safety limit for fresh meat. Combined with the results of antibacterial and bacterial adhesion experiments, it shows that the composite coating can kill spoilage bacteria attached to the pork surface through the synergistic bactericidal effect of chitosan-ion release. At the same time, the hydrophobic interface reduces bacterial colonization and adsorption, significantly slowing down the growth rate of the total colony count.
[0168] Comparing the effects of antibacterial papers prepared in Examples 1-3 and 1-4 (S-CS, S-CSD, S-CSG, S-CSDG, S-CSDGA-5, S-CSDGA-10, and S-CSDGA-15) on pork preservation at room temperature and 4°C, the results are as follows: Figure 17 , Figure 18As shown, with prolonged storage, the grapes in the room-temperature control group suffered severe water loss and shriveling, with obvious stem drying and browning, mold growth, and pulp rot. Refrigeration reduced grape respiration and mold growth, delaying the spoilage time in the control group, but problems such as darkened skin and soft berries persisted. Modified antibacterial paper with added DES and glycerol only slightly delayed grape deterioration. The antibacterial paper prepared in Examples 1-3, on the one hand, incorporates Ag / ZIF-8 / g-C3N4 nanomaterials that release antibacterial substances to inhibit the proliferation of putrefactive bacteria such as gray mold; on the other hand, the protective barrier constructed by the coating reduces oxidative damage to the skin. Grape weight loss is mainly caused by water loss due to fruit respiration and transpiration. Raw sugarcane paper is hydrophilic and porous, unable to retain moisture lost from grapes, leading to continuous water loss and a sustained increase in weight loss. The composite coating improves the moisture permeability of the sugarcane paper, forming a moderately breathable and moisture-proof barrier. This prevents high humidity and mold growth inside the packaging while effectively reducing the rate of water loss through transpiration from the grapes. A low temperature of 4℃ significantly reduces the respiratory metabolic intensity of the grapes, resulting in lower weight loss rates in all groups compared to storage at room temperature. The initial pH of grape pulp is in a stable, slightly acidic range. During storage, the decomposition of sugars and organic acids by microorganisms causes a rise in pH; the higher the degree of fruit decay, the more significant the pH change. In the control group, the pH of grapes continuously increased over storage time under both ambient and 4℃ refrigeration conditions, indicating that a large amount of organic acids inside the fruit were consumed and microbial metabolic activity was vigorous. The composite-coated antibacterial paper can inhibit the growth and reproduction of putrefactive microorganisms and molds on the surface and in the crevices of grapes, slow down the decomposition and consumption of organic acids, effectively maintain the pH level of grapes, and preserve the original flavor and quality of grapes to the greatest extent. The 4℃ refrigeration condition can work with the antibacterial materials to further stabilize the pH value of the pulp, resulting in better preservation.
[0169] IV. Blood Biocompatibility
[0170] The blood compatibility of the film samples and antibacterial paper samples prepared in Examples 1-3, Application Examples 1-3, and Comparative Examples 1-4 was evaluated using a hemolysis test. A hemolysis rate of <5% was considered acceptable as no hemolysis and satisfactory blood compatibility. The specific experimental methods are as follows:
[0171] Blood was collected from the orbital cavity of mice. Fresh mouse blood was added to a centrifuge tube containing 200 µL of sodium citrate anticoagulant and centrifuged at 3000 r / min for 5 min. The supernatant was discarded, and the blood was resuspended in sterile 0.9% (w / v) NaCl solution and centrifuged at 3000 r / min for 5 min. This process was repeated three times. The supernatant was discarded, and the red blood cells in the lower layer were resuspended in sterile 0.9% (w / v) NaCl solution to prepare a 4% (v / v) red blood cell suspension for later use. The membrane sample and sugarcane-based antibacterial paper were cut into small pieces and immersed in sterile 0.9% (w / v) NaCl solution for 12 h. The extract and the red blood cell suspension were co-cultured. A 0.9% (w / v) NaCl solution was set up as a negative control group, and 1% (v / v) Tritium solution was set up as a positive control group. Incubate in a constant temperature water bath at 37℃ for 30 min, protected from light, to simulate the physiological environment of the human body. After centrifugation, collect 200 µL of the supernatant and measure the absorbance at 540 nm to calculate the hemolysis rate of red blood cells.
[0172] (6)
[0173] Among them, OD 阴 OD 阳 These are the absorbance values corresponding to the 0.9% NaCl and 1% Triton groups, respectively.
[0174] The hemolysis rates of the CSDGA-5, CSDGA-10, and CSDGA-15 films prepared with the film-forming solutions of Examples 1-3, and the CS, CSD, CSG, and CSDG films prepared with the film-forming solutions of Comparative Examples 1-4 are as follows: Figure 19 The hemolysis rates of antibacterial paper samples prepared in Examples 1-3 and 1-4 (S-CS, S-CSD, S-CSG, S-CSDG, S-CSDGA-5, S-CSDGA-10, and S-CSDGA-15) were compared using Examples 1-3. Figure 20 As shown in the figure. 1% (v / v) Triton was used as a positive control, resulting in complete rupture of red blood cells and release of hemoglobin, with a hemolysis rate approaching 100%. 0.9% (w / v) NaCl saline was used as a negative control, showing intact red blood cell structure with almost no hemolysis. The hemolysis rates of all films and sugarcane-based antibacterial paper were significantly lower than the 5% safety threshold. The supernatant in each group was clear and transparent, with only intact red blood cell sediment remaining at the bottom of the tube, and no obvious hemoglobin dissolution or reddening. This demonstrates that the films and sugarcane-based antibacterial paper do not cause damage to red blood cells. This indicates that the sugarcane-based antibacterial paper prepared in this study possesses excellent blood compatibility and will not release irritating or hemolytic toxic substances into the food system during the packaging of fresh pork and grapes. It is safe and non-toxic, meeting the requirements for food contact materials, and providing a safety basis for the practical application of this material in fresh food packaging.
[0175] V. Soil Degradation Experiment
[0176] The soil burial method was used to investigate the natural soil degradation performance of antibacterial papers (S-CS, S-CSD, S-CSG, S-CSDG, S-CSDGA-5, S-CSDGA-10, and S-CSDGA-15) prepared in Application Examples 1-4, evaluating their biodegradability and environmental friendliness. Sugarcane-based base paper was used as a control group. Sugarcane-based antibacterial paper samples were cut to uniform sizes and buried at a uniform depth of 3–5 cm, ensuring uniform soil coverage without any exposed areas. Changes on the surface of the sugarcane-based antibacterial paper, including cracking, breakage, and pore formation, were observed and recorded regularly to visually describe the film-soil degradation process.
[0177] Experimental results are as follows Figure 21 As shown, sugarcane-based antibacterial paper exhibited good natural degradation characteristics during soil landfilling. With prolonged landfilling time, the intact structure of the paper was gradually destroyed, with the surface becoming loose, cracked, and even broken, indicating a continuously increasing degree of degradation. After 14 days of landfilling, all antibacterial paper had completely degraded. The main component of sugarcane-based paper is natural plant fiber, which can be effectively decomposed and utilized by microorganisms and enzymes in the soil, possessing excellent biodegradability. The sugarcane-based antibacterial paper in the control group and all experimental groups completely degraded within the same timeframe, indicating that the addition of nanomaterials, DES, and glycerol did not hinder the degradation process of the fiber matrix and had no significant negative impact on the overall degradation performance of the paper. As the degradation reaction continued, the sugarcane-based antibacterial paper could be gradually decomposed and assimilated by soil microorganisms, without producing recalcitrant waste residues. These results demonstrate that the prepared sugarcane-based antibacterial paper possesses excellent soil degradability and good environmental compatibility, meeting the requirements for sustainable application of green materials.
Claims
1. A method for preparing a composite antibacterial film-forming liquid, characterized in that, Includes the following steps: (1) Dissolve chitosan in an aqueous acetic acid solution to obtain a chitosan solution; (2) Add a eutectic solvent to the chitosan solution, stir at room temperature, then add glycerol and stir until the solution is uniform and transparent to obtain a CSDG solution; wherein, (3) Add the Ag / ZIF-8 / g-C3N4 composite material to a CSDG solution accounting for 10%-30% of the total mass of the CSDG solution and ultrasonically disperse until there is no obvious agglomeration. Then add the remaining CSDG solution and stir at room temperature until the system is uniform to obtain the composite antibacterial film-forming liquid.
2. The method for preparing the composite antibacterial film-forming liquid according to claim 1, characterized in that, In step (1), the ratio of chitosan to the aqueous acetic acid solution is 0.5-1.0 g: 50 mL, and the aqueous acetic acid solution is a 0.5% (v / v) glacial acetic acid aqueous solution.
3. The method for preparing the composite antibacterial film-forming liquid according to claim 1, characterized in that, In step (2), the eutectic solvent is composed of choline chloride and citric acid in a molar ratio of 1:
1.
4. The method for preparing the composite antibacterial film-forming liquid according to claim 1, characterized in that, In step (2), the amount of the eutectic solvent added is 20%-40% of the mass of the chitosan, and the amount of glycerol added is 20%-50% of the mass of the chitosan; in step (3), the mass-volume ratio of the Ag / ZIF-8 / g-C3N4 composite material to the total amount of the CSDG solution is 5-15 mg:50 mL.
5. The method for preparing the composite antibacterial film-forming liquid according to claim 1, characterized in that, The Ag / ZIF-8 / g-C3N4 composite material is prepared by the following steps: 1) g-C3N4 was prepared by calcining melamine as a precursor at 500-600℃ for 3-5 h. Then, g-C3N4 was ultrasonically dispersed in methanol to obtain g-C3N4 dispersion. 2) ZIF-8 was prepared by reacting 2-methylimidazole and zinc nitrate hexahydrate in methanol at a molar ratio of 8:1; ZIF-8 was then ultrasonically dispersed in methanol to obtain a ZIF-8 dispersion. 3) Add the ZIF-8 dispersion from step 2) to the g-C3N4 dispersion from step 1) and mix and stir. Then add AgNO3 and continue stirring. Subsequently, add ascorbic acid and continue stirring and reacting. After solid-liquid separation and drying, the Ag / ZIF-8 / g-C3N4 is obtained. The mass ratio of g-C3N4, ZIF-8, AgNO3 to ascorbic acid is 4:1:1.7:0.
88.
6. The method for preparing the composite antibacterial film-forming liquid according to claim 1, characterized in that, The eutectic solvent is prepared by mixing choline chloride and citric acid in a molar ratio of 1:1 and stirring in a water bath at 75-85°C until a colorless, transparent, and homogeneous liquid is formed.
7. A composite antibacterial film-forming liquid, characterized in that, Prepared by the method described in any one of claims 1-6.
8. An antibacterial paper, characterized in that, The antibacterial paper is prepared by pre-treating packaging paper, immersing it in the composite antibacterial film-forming liquid described in claim 7, removing it, spreading it out, and drying it.
9. The antibacterial paper according to claim 8, characterized in that, The pretreatment involves soaking the packaging paper in a 75% (v / v) ethanol solution to dewax it, rinsing it with deionized water, and drying it at 35-45°C. The soaking time is 0.5-2 hours, and the drying is done by air drying at room temperature.
10. Use of the antibacterial paper according to claim 8 or 9 in food packaging materials.
